1998
DOI: 10.1093/oxfordjournals.jbchem.a022050
|View full text |Cite
|
Sign up to set email alerts
|

Properties, Sequence, and Synthesis in Escherichia coli of 1-Aminocyclopropane-l-Carboxylate Deaminase from Hansenula saturnus

Abstract: The plant hormone ethylene is generated from a unique precursor, 1-aminocyclopropane-1-carboxylate (ACC). In previous studies, ACC deaminase, which degrades ACC to alpha-ketobutyrate and ammonia, was found in four strains of Pseudomonas, characterized, and sequenced. To verify the wider distribution of ACC deaminase in microorganisms, we purified and sequenced ACC deaminase from the yeast Hansenula saturnus. The purified enzyme was active toward ACC, D-serine and dl-coronamic acid, indicating the same stereosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…It has been previously suggested that the PLP-binding regions in these enzymes share the same fold, which consist of two domains (33). Some of the earliest descriptions of the structural attributes of yACCD based on a sequence comparison with TRPS␤ (16% identities in sequences) also suggested that the fold of yACCD would bare some similarity to that of TRPS␤ (11). On the other hand, the sequence comparisons of yACCD with TD and OASS detected (if any) very limited similarity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously suggested that the PLP-binding regions in these enzymes share the same fold, which consist of two domains (33). Some of the earliest descriptions of the structural attributes of yACCD based on a sequence comparison with TRPS␤ (16% identities in sequences) also suggested that the fold of yACCD would bare some similarity to that of TRPS␤ (11). On the other hand, the sequence comparisons of yACCD with TD and OASS detected (if any) very limited similarity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallization and Data Collection-The yACCD was purified and crystallized as described previously (11,13). Mercury derivatives of yACCD were obtained by co-crystallization with 0.5 mM p-hydroxymercuribenzene sulfonate (PHMBS) using the hanging drop vapor diffusion method.…”
Section: Methodsmentioning
confidence: 99%
“…ACP and the yeast Cyberlindnera saturnus (previously Hansenula saturnus) were the two first microorganisms reported to synthesize ACC deaminase (Honma and Shimomura, 1978;Minami et al, 1998). Subsequently, ACC deaminase activity has been found in numerous bacteria, both gram positive and negative with a variety of different types of metabolism (for review, see Gamalero and Glick, 2012;Glick, 2014).…”
Section: Distribution and Phylogeny Of Acc Deaminasementioning
confidence: 99%
“…The gene encoding this enzyme has been isolated from a few strains of Pseudomonas spp., Rhizobium leguminosarum of the yeast Hansenula saturnus, and the fungus Penicillium citrinum. The crystal structure has been determined for the yeast (15) and bacterial (12) ACC deaminase enzymes; the biochemical and thermodynamic properties of the ACC deaminase from Pseudomonas putida UW4 have been measured (10). Here, using PCR with degenerate primers, we have successfully isolated ACC deaminase genes from a range of both gram-positive and gram-negative bacterial species.…”
mentioning
confidence: 99%